Do dogs form reputations of humans? No effect of age after indirect and direct experience in a food-giving situation - Hoi-Lam Jim; Kadisha Belfiore; Eva B. Martinelli; Mayte Martínez; Friederike Range; Sarah Marshall-Pescini (Animal Cognition, 2025)
Abstract Animals can form reputations of individuals through direct interactions or by observing interactions with a third party, known as eavesdropping. Given their cooperative relationship with humans, considerable interest has focused on whether dogs (Canis lupus familiaris) can socially evaluate humans, though findings remain mixed. To assess whether this ability develops during ontogeny, we investigated whether dogs of different ages (young, adult, and senior) can form reputations of humans after observing them interact with a conspecific or through direct interactions in a food-giving situation. Forty pet dogs participated in the experiment. In the eavesdropping condition, dogs observed two humans interact with a dog demonstrator—one was generous and fed the dog, while the other was selfish and withheld food. In the direct experience condition, dogs interacted with the two partners directly. We analysed dogs’ first choice and time spent exhibiting affiliative behaviours towards each partner. Results showed that dogs across all age groups did not significantly prefer the generous partner compared to the selfish partner, nor did their behaviour exceed chance levels following indirect or direct experience. These findings do not provide support for dogs showing reputation formation and highlight the methodological complexities of studying this phenomenon.